Low cost configuration of SRAM based ALTERA devices - Jaquenod, Guillermo A. (2002)
During device operation, SRAM based ALTERA devices store configuration data in volatile SRAM cells, therefore that information must be reloaded each time the device powers up. The configuration data to be loaded must be retrieved from some non-volatile source such as special configuration memories or external sources, using different configuration schemes.\nThe use of Configuration devices is very direct and simple, but these benefits are sometimes obscured by its cost, that can get over the cost of the device to be configured. The other configuration methods are a bit more complex and require the use of some I/O pins of an external microprocessor, but they can be useful to attain simple and cheap configuration methods.\nThis paper describes the use of standard, very low cost serial EEPROM memories for configuration, using minimum microprocessor resources, in Passive Serial Configuration mode; in this case, the EEPROM memory can be used not only to store configuration data but also some other non-volatile information required by the microprocessor.